Molecular Mechanisms of Neuropathic Pain (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint is a compilation of papers published in the Cells Special Issue "Molecular mechanisms of neuropathic pain." Particularly important themes include sex differences and brain–immune connections in the molecular mechanisms of fibromyalgia and neuropathic pain. Furthermore, the updated discoveries of well-known mechanisms through microglia, BDNF, and LPA receptor signaling are noteworthy.